2020
DOI: 10.1039/c9ob02663k
|View full text |Cite
|
Sign up to set email alerts
|

Squaramide-catalysed asymmetric cascade reactions of 2,3-dioxopyrrolidines with 3-chlorooxindoles

Abstract: An efficient squaramide-catalysed asymmetric Michael addition/cyclization cascade reaction of 3-chlorooxindoles with 2,3-dioxopyrrolidines produced the corresponding chiral spiro-compounds in high yields with excellent stereoselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Later in 2020, Du reported a related reaction using this time 3‐chlorooxindoles as pronucleophiles. Again, the reaction was catalyzed by a bifunctional squaramide derivative of quinine C14 [80] . The authors found that the presence of one equivalent of NH 4 HCO 3 was crucial to obtain the desired bi‐spirocyclic products in high yields, diastereoselectivities and enantiomeric excesses (Scheme 51).…”
Section: ‐Ylidene‐23‐dioxopyrrolidinesmentioning
confidence: 99%
“…Later in 2020, Du reported a related reaction using this time 3‐chlorooxindoles as pronucleophiles. Again, the reaction was catalyzed by a bifunctional squaramide derivative of quinine C14 [80] . The authors found that the presence of one equivalent of NH 4 HCO 3 was crucial to obtain the desired bi‐spirocyclic products in high yields, diastereoselectivities and enantiomeric excesses (Scheme 51).…”
Section: ‐Ylidene‐23‐dioxopyrrolidinesmentioning
confidence: 99%
“…Chiral squaramide has been shown to successfully catalyze several reactions including Michael additions, and the Mannich, aza-Henry, and Strecker reactions. Moreover, these catalysts have successfully produced enantio-enriched products in single and domino/cascade reactions in various asymmetric organic transformations [168][169][170][171][172][173][174][175][176].…”
Section: Squaramide Catalystmentioning
confidence: 99%
“…图式 5 3-氨基氧吲哚与乙烯基磺酰氟的 Michael/环化串联反 应 Scheme 5 Michael/cyclization cascade reactions of 3-aminooxindoles with ethylene sulfonyl fluorides 他骨架底物, 分别于 2019 年 [21] 和 2020 年 [22] (1) R 1 = CO 2 Et, CO 2 Me, Boc; R 2 = Boc, Me, Bn, Ac; R 3 = 5-OMe, 5-Cl, 6-Cl, 7-Cl, 5-NO 2 ; R 4 = Ph, 4-ClC 6 H 4 , 4-MeOC 6 H 4 , Me; R 5 = 6-Cl, 6-OMe, 7-OMe, 5-OH 随后, 2018 年, 本课题组 [28] 9.2 3-三氟乙基亚胺氧吲哚参与的不对称 1,3-偶极环 化串联反应 同年, 王锐等 [39] 利用本课题组所开发的新型氧吲 哚串联反应试剂 3-三氟乙基亚胺氧吲哚 2g [40] 2017 年, 鲁桂课题组 [43] 利用 3-亚甲基氧吲哚 2b 与 3-三氟乙基亚胺氧吲哚 2g 反应, 报道了一例选择性环 外 1,3-偶极环化串联反应(Scheme 19a). 在奎宁衍生的 方酰胺 C14 催化作用下, 以高度立体选择性的方式有效 地构建了一系列潜在的具有重要生物学意义的含三氟 甲基的吡咯烷基螺环双氧吲哚产物 80 (84%~99%的产 率, 高达>20∶1 dr 和>99% ee).…”
Section: 方酰胺催化的不对称 Michael/环化串联反应unclassified